Generic and family transfers, and numina dubia for orb-weaving spiders (Araneae, Araneidae) in the Australasian, Oriental and Pacific regions - Volker W. Framenau (Evolutionary Systematics, 2019)
As part of a current revision of the Australasian and Pacific orb-weaving spider fauna (family Araneidae Clerck, 1757), a number new combinations are proposed in the genera Acroaspis Karsch, 1878 (3 species), Carepalxis L. Koch, 1872 (1 species), Cyclosa Menge, 1866 (5 species), and Neoscona Simon, 1864 (7 species): Acroaspis lancearia (Keyserling, 1887), comb. n., A. mamillana (Keyserling, 1887), comb. n., A. scutifer (Keyserling, 1886), comb. n., Carepalxis furcifera (Keyserling, 1886), comb. n.; Cyclosa anatipes (Keyserling, 1887), comb. n.; Cyclosa apoblepta (Rainbow, 1916), comb. n.; Cyclosa argentaria (Rainbow, 1916), comb. n.; Cyclosa lichensis (Rainbow, 1916), comb. n.; Cyclosa poweri (Rainbow, 1916), comb. n.; Neoscona decolor (L. Koch, 1871), comb. n.; Neoscona enucleata (Karsch, 1879), comb. n.; Neoscona flavopunctata (L. Koch, 1871), comb. n.; Neoscona floriata (Hogg, 1914), comb. n.; Neoscona granti (Hogg, 1914), comb. n.; Neoscona inusta (L. Koch, 1871), comb. n.; and Neoscona notanda (Rainbow, 1912), comb. n. The following two Australian species, currently placed in Araneus, are not Araneidae but comb-footed spiders (family Theridiidae Sundevall, 1833): Anelosimus dianiphus (Rainbow, 1916), comb. n. and Theridion xanthostichus (Rainbow, 1916), stat. and comb. n. The following six species are considered numina dubia as their type material is immature or otherwise unidentifiable (e.g. partly destroyed): Araneus acachmenus Rainbow, 1916; Araneus agastus Rainbow, 1916; Araneus exsertus Rainbow, 1904; Araneus suavis Rainbow, 1899; Carepalxis coronata (Rainbow, 1896); and Heurodes turritus Keyserling, 1886. Heurodes fratellus (Chamberlin, 1924) is considered a nomen dubium and Heurodes porcula (Simon, 1877) is returned to Eriovixia Archer, 1951, Eriovixia porcula (Simon, 1877). Type material of predominantly Australian species described by E. v. Keyserling (1 species), W. J. Rainbow (10 species), A. T. Urquhart (8 species), and C. A. Walckenaer (2 species) is here considered destroyed or otherwise lost. As it is impossible to identify these species from their original descriptions and considering the known spider fauna from their respective type localities, they are all considered numina dubia: Anepsia crinita Rainbow, 1893; Epeira diabrosis (Walckenaer, 1841); Epeira diversicolor Rainbow, 1893; Epeira ficta Rainbow, 1896; Epeira hamiltoni Rainbow, 1893; Epeira lacrymosa (Walckenaer, 1841); Epeira leai Rainbow, 1894; Epeira mortoni Urquhart, 1891; Epeira notacephala Urquhart, 1891; Epeira obscurta Urquhart, 1893; Epeira phalerata Urquhart, 1893; Epeira pronuba Rainbow, 1894; Epeira rara Keyserling, 1887; Epeira singulara Urquhart, 1891; Epeira sub-flavida Urquhart, 1893; Epeira similaris Rainbow, 1896 (= Araneus urquharti Roewer, 1942 replacement name); Epeira ventriosa Urquhart, 1891; and Epeira viridula Urquhart, 1891.